PENERAPAN MODEL INTERACTIVE LECTURE DEMONSTRATIONS (ILD) BERBANTUAN SIMULASI KOMPUTER UNTUK MENURUNKAN KUANTITAS MISKONSEPSI PESERTA DIDIK DAN PENGUBAHAN KONSEPSI PADA MATERI GELOMBANG CAHAYA - Adam Hadiana Aminudin, - (2019)
Misconception is one of the problems that is still found in the material of light waves. These problems can be obstacles in the learning process, especially in the abstract material. The study aims to decrease the quantity of students' misconceptions and conceptual change on light wave material. The method used is a mixed-method with an explanatory sequential mixed methods design. The instrument used was a four-tier instrument developed based on alternative conceptions of students on light wave. Participants in this study numbered 46 students (average age 17 years old) in one of Indramayu City high schools. Participants consisted of 22 students in the experimental class, and 24 students in the control class. Students in the experimental class use the Interactive Lecture Demonstrations (ILD) model with computer simulations. While the control class without the computer simulations. The result, a decreased quantity of students' misconception in the experimental class was higher than the control class. In sequence, the value obtained was 0,83 with a high category and 0,42 in the moderate category. Likewise for the conceptual change, in the Acceptable Change category, the experimental class was higher than the control class, with percentages of 69% and 48%, respectively. The other categories, such as No Change and Not Acceptable were dominated by the control class, with percentages of 34% and 18%. While the experimental classes were 25% and 6%, respectively. The effect size calculation results show that the implementation of the ILD model with computer simulations has an impact of 0,71 in the large category. Thus, ILD models with computer simulations can be used as an alternative to decrease the quantity of students' misconceptions and conceptual change on light wave material.